Authoritarian Neoliberalism and Resistance in Turkey
XIX, 234 p. 3 illus., 2 illus. in color.
Keywords: “These well-researched articles draw a striking and timely picture, at the ground level, of a regime that has become a conduit for plunder and dispossession. The authors describe an arena where authoritarian repression of criticism and opposition has grown, but resistance has also been mounting. The unique focus on resistance of this excellent collection injects a much-needed note of optimism into the literature.” – Çağlar Keyder, Professor of Sociology, State University of New York, Binghamton “Has neoliberalism been in decline in the past decade? Is resistance against authoritarian governments no longer possible? In response to both questions, Authoritarian Neoliberalism and Resistance in Turkey convincingly says no!” – Deniz Yükseker, Editor, New Perspectives on Turkey “This exemplary edited collection adds depth and clarity to our understanding of the dynamics of authoritarian neoliberalism in Turkey, as well as providing insights applicable beyond the Turkish case. It does so through the combination of a clear and systematic conceptual framework on consolidating and contesting authoritarian neoliberalism.” – Yunus Sözen, Assistant Professor of Political Science, Le Moyne College This book offers new clarity on three important political concepts: authoritarianism, neoliberalism, and resistance. While debates on authoritarian resurgence have been limited to the examination of political factors (e.g., polarisation, conflict) until recently, the rising literature on ‘authoritarian neoliberalism’ highlights how the neoliberal restructuring of political economy bolsters the authoritarian tendencies of elected governments both in the Global South and the Global North. This book will be an invaluable resource not only to scholars of Turkey and the Middle East but also to researchers into authoritarianism and neoliberalism around the world. Dr İmren Borsuk is a ResearchFellow at the Berlin Forum Transregionale Studien and Stockholm University. Dr Pınar Dinç is a Researcher at the Centre for Advanced Middle Eastern Studies, Lund University. Dr Pınar Sayan is an Assistant Professor at the Department of Political Science and International Relations, Beykoz University. Dr Sinem Kavak is a Research Affiliate at Lund University. Chapters 2 and 10 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.